Analysis of the Supply Chain Disruption Risks in the Malaysian Automotive Remanufacturing Industry- a Case Study - Hishamuddin, Hawa; Mat Ropi, Nuramilawahida; Abd Wahab, Dzuraidah (International Journal of Integrated Engineering, 2020)
Remanufacturing has now become one of the effective strategies for reducing the negative impact on the environment by prolonging the products’ life cycle in the automotive sector. Still considered as a relatively new industry in Malaysia, the low remanufacturing rate coupled with the lack of standardization are thus seen as causing a high inclination of disruption occurrences in the remanufacturing operations. As such, this paper had identified and investigated the existing disruptions in four problematic areas, namely the production planning, infrastructure facilities, distribution networking and inventory management of the automotive remanufacturing firms in Malaysia. From the SPSS analysis and calculation of the mean and standard deviation values on the semi-structured interviews that were conducted in three remanufacturing companies, the highest contributor to the disruption risks was found to have resulted from the difficulty in obtaining the spare parts components in the production planning process. By also exploring the awareness level on environmental sustainability and the significance of remanufacturing processes among the remanufacturer companies, this analysis is thus deemed useful for not only identifying suitable actions that can be taken for mitigating the various risks faced by the automotive remanufacturers in Malaysia, but also in solving the disruptions of the remanufacturing supply chain system.